Revaluation fantasy - Fabian Muniesa (Finance and Society, 2023)
Financial conspiracies today blend together antisemitic tropes and spiritual visions with ideals of political reform and economic salvation. It is tempting to locate such phenomena at the periphery of the financial order, situating them within a delusional space beyond judicious concepts of money, finance, wealth, and value. But is also possible to take paranoid finance as an extreme, radical appropriation of a logic inherent in finance.
Keywords: 300; conspiracy; Financial imagination; GESARA; NESARA; paranoia; valuation